PENINGKATAN PERAN KONSELOR DI BIDANG KESEHATAN PADA PUSAT INFORMASI KONSELING GIBITA DAN KARANG TARUNA LINGGASARI - Atyanti Isworo; Endang Triyanto; Wahyu Ekowati (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2020)
The number of adolescents in the Purwokerto area is the third highest in the Central Java Province. Adolescence is very closely related to the puberty period which is accompanied by sexual development. This condition makes adolescents are prone to various forms of behavioral problems, such as having sex before marriage and drug abuse, both of which can carry risks to HIV / AIDS transmission. It is very important to instill good morale in the younger generation through youth organizations, such as youth organizations and counseling information centers. However, teenage health problems were found, especially in the area of Linggasari Youth Center and the â€œGibitaâ€ Information Counseling Center/ Pusat Informasi Konseling (PIK) such as lack of understanding of HIV / AIDS, the dangers of smoking, and adolescent reproductive health. To overcome this problem, we trained Adolescent Counselors. Classroom learning, problem based solving, participatory learning, role play were used in this project. The result revealed that this activity enhances the understanding of knowledge and skills of new counselors on adolescent health problems. In addition, we also produced modules and film (roleplay and educational videos) of adolescent health problems counseling.